Competency Problems of Halal Slappers In Indonesia: A Literature Study - Rizky Andrean; Hendri Hermawan Adinugraha (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2021)
The majority of the Indonesian population is Muslim, so there is an obligation to consume halal food, including slaughtered products. This study aims to examine and identify the competency problems of halal slaughterers in Indonesia. The method in this research is an empirical study of phenomenology and also descriptive analysis in the form of library research using a qualitative research approach. This study uses secondary data derived from articles, books, internet, previous studies, and other reference sources that are relevant to the thing being studied. The results of the study indicate that the main problem in the competence of halal butchers in Indonesia is the lack of access and opportunities for slaughterers to attend training and competency tests (certification) of halal slaughterers.